REVOLT AGAINST THE DOMINATION OF PATRIARCHIC CULTURE: A CRITICAL DISCOURSE ANALYSIS ON CARMEN BIN LADIN'S INSIDE THE KINGDOM - AFIANA, Destian (2011)
The purposes of the research are to describe the revolt against the domination of patriarchic culture reflected in Inside the Kingdom based on its structural elements and to reveal the dominant ideology reflected. This research is the type of descriptive qualitative research that uses two data, namely primary and secondary data. The primary data is Inside the Kingdom autobiography written by Carmen bin Ladin, while the secondary data is from other sources that support the analysis such as books and journals. Using Critical Discourse Analysis as the theoretical framework, the research shows the following findings. First, the structural elements of Inside the Kingdom are evidence that there is revolt from Carmen as Western woman toward Patriarchic culture in Saudi Arabia. It is proven by Carmen's emphasizing on the negative presentation about the culture of Saudi Arabia. Second, the dominant ideology n Inside the Kingdom is feminist ideology. This ideology is reflected through the several key issues that remark Inside the Kingdom as a feminist discourse.